A global phylogeny of Lycopodiaceae (Lycopodiales; lycophytes) with the description of a new genus, Brownseya, from Oceania. Issue 1 (6th November 2021) - Chen, De‐Kui; Zhou, Xin‐Mao; Rothfels, Carl J.; Shepherd, Lara D.; Knapp, Ralf; Zhang, Liang; Lu, Ngan Thi; Fan, Xue‐Ping; Wan, Xia; Gao, Xin‐Fen; He, Hai; Zhang, Li‐Bing
Abstract: Lycopodiaceae are one of the oldest lineages of any living vascular plants and contain about 400 species distributed on all continents except Antarctica, with its highest diversity in tropical regions. Previous studies on the morphology, anatomy, and molecular systematics of Lycopodiaceae have made substantial progress in understanding the diversity and evolution of the family, but major issues remain. In particular, earlier studies had relatively sparse taxon sampling, some critical relationships among the genera have not been well resolved, and the monophyly of some genera (e.g., Huperzia, Lycopodiella, Pseudolycopodiella, Spinulum ) has not been robustly tested with large sampling. In this study, we apply maximum likelihood, maximum parsimony, and Bayesian inference to a dataset of 1150 (918 newly generated) DNA sequences of seven plastid markers ( atpA, psbA‐trnH, rbcL, rps4, rps4‐trnS, trnL, trnL‐F ) of 334 accessions representing ca. 155 (ca. 39% of all) species in the family to infer a global phylogeny. Our major results include: (1) the tree is resolved into three primary clades corresponding to the three subfamilies, Huperzioideae, Lycopodioideae, and Lycopodielloideae; (2) these three primary clades are resolved into 17 major clades, of which 16 represent genera recognized in the PPG I classification, while Lycopodiella serpentina is resolved as sister to Palhinhaea, and thus a new genus, Brownseya, is described, and a key to genera of Lycopodielloideae is given; (3) Phylloglossum is strongly or moderately supported as sister to Phlegmariurus in ML and MP analyses (but not in BI analysis), and thus our evidence supports the recognition of Phlegmariurus in order to maintain a monophyletic Huperzia ; (4) Lycopodiella is sister to Pseudolycopodiella and they together are sister to Lateristachys  + ( Brownseya +  Palhinhaea ); (5) Huperzia, Lycopodiella, Pseudolycopodiella, and Spinulum are each strongly supported as monophyletic; (6) spore morphology is well consistent with the phylogenetic relationships in the family; and (7) based on these results we recognize 17 genera in three subfamilies in the family.